Selected Papers from the Eurasian Conference on Educational Innovation 2019 - Teen-Hang Meen; Charles Tijus; Chun-Yen Chang (MDPI AG, 2019)
The Second Eurasian Conference on Educational Innovation 2019 (ECEI 2019) was held in Singapore on 27−29 January 2019, and provided a communication platform for researchers on the topic of educational innovations [...]